Analisis Financial Distress dengan Metode Altmanz-Score pada Sub Sektor Perikanan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2013-2017 - Nurhikmah Aljufri (Universitas Batanghari Jambi, 2019)
This study aims to determine the potential, ranking of financial distress in the fisheries sub-sector which is listed on the Indonesia Stock Exchange (IDX) 2013-2017 period. In this study the research sample was taken using purposive sampling technique. From these techniques there were 3 companies namely PT. Central Proteina Prima Tbk, PT. Dharma Samudera Fishing Industries Tbk, and PT. Inti Agri Resource Tbk. Next to analyze how the potential and ranking of financial distress data is processed using the Altman Z-score analysis tool. The results of this study indicate that by using the Altman Z-score method from three companies that were used as research samples there were PT. Dharma Samudera Fishing Industries Tbk for the last 5 years in the gray area position, PT. Central Proteina Prima Tbk in 2016 and 2017 is in a bankrupt position, and PT. Inti Agri Resources Tbk in 2016 and 2017 can improve its financial position with tinsel in a position not bankrupt Keywords: financial distress, Altman Z-score, fisheries sub-sector